Effect of N-isopropylacrylamide on the preparation and properties of microencapsulated phase change materials. (1st July 2016) - Li, Dan; Wang, Jianping; Wang, Yanan; Li, Wei; Wang, Xuechen; Shi, Haifeng; Zhang, Xingxiang
Abstract: NIPAm (N-isopropylacrylamide), a thermosensitive monomer, was introduced into a system for synthesis of MicroPCMs (microencapsulated phase change materials) through free radical emulsion polymerization with n-oct (n-octadecane) as the core and cross-linked PMMA (poly (methyl methacrylate)) as the shell. The effect of NIPAm on the formation mechanism, surface morphologies, crystallization properties, and thermal stabilities of the MicroPCMs were studied using FTIR (Fourier transform infrared spectroscopy), SEM (scanning electron microscopy), DSC (differential scanning calorimetry), and TGA (thermogravimetric analysis), respectively. The results indicate that addition of NIPAm causes a significant increase in the enthalpy of the heterogeneous nucleation (approximately 2–4 times more than without NIPAm). The diameter distribution of microcapsules becomes narrower (the PDI (polydispersity index) has a minimum of 0.073) and the encapsulation ratio and encapsulation efficiency increase. On the contrary, the microcapsules that have some irregular holes were obtained by adding NIPAm prepolymer. Graphical abstract: Highlights: We designed and synthesized a lower supercooling microPCMs with the PNIPAm as nucleating agent. Optimum dosage of monomer PNIPAm is 1.8 g. The mass loss of microcapsules is less than 0.6% after repeated thermal cycling. The formation mechanism of the microcapsules is discussed.